Profil Pemecahan Masalah Matematika Dalam Menyelesaikan Permasalahan Pemrograman Linear Ditinjau Dari Kemampuan Komunikasi Matematis Mahasiswa - Dwi Erna Novianti (Universitas PGRI Madiun, 2017)
This qualitative descriptive study aimed to describe the profile of math problem solving based on mathematic communication. This research was conducted at Mathematic department IKIP PGRI Bojonegoro. Selection of subjects using a questionnaire mathematic communication is classified as high, medium, and low. Analysis of data over the troubleshooting tests, questionnaires and interviews, as well as the validity of test data using triangulation of data sources and triangulation techniques. Based on the results of the research: 1) Students who have high levels of mathematic comunication high differ in solving a mathematical problem that is at the stage of understanding the issue and re-examine the final answer, 2) Students are who have medium levels of mathematic communication having the difference in solving a mathematical problem that is at the stage of planning completion, implementation settlement plan, and phase re-examine the final answer, 3) students are who have low levels of mathematic communication having the difference in solving a mathematical problem that is at the stage of understanding the problem and students were less confident when solving problems.